Optimasi Formula Sediaan Minyak Telon Bayi Tree Tea Oil (Melaleuca alternifolia Cheel) dengan Variasi VCO dan Olive Oil dengan Metode Simplex Lattice Design - Adityas, Hanung Puspita; Wulansari, Eka; Sari, Rizka Noviana (Jurnal Farmasi & Sains Indonesia, 2024)
One of the plants that can be used as a natural medicine is the tea tree plant (Melaleuca alternifolia Cheel) which is generally known as the tea tree. The tea tree plant contains essential oils which are useful as antimicrobial and anti-inflammatory. Another plant that can be used as a natural ingredient is the fennel plant (Foeniculum vulgare Mill) which contains essential oils which are useful as antimicrobials. In order to develop the preparation, a telon oil preparation was formulated. The use of additional ingredients in the formulation of telon oil preparations, namely VCO and Olive Oil as vegetable oils which function as solvents for essential oils, can certainly affect the physical properties of telon oil preparations, so a method is needed to find an optimum formula that meets the good physical properties of the preparation. This research aims to determine the optimum formula composition of telon oil preparations with variations of VCO and Olive Oil using the Simplex Lattice Design method by looking at the results of evaluation tests of the physical properties of telon oil preparations which include organoleptic tests, homogeneity tests, pH tests, specific gravity tests, viscosity tests and displaced volume test. The results of organoleptic tests, homogeneity, pH, specific gravity, viscosity and transferred volume have met the requirements. Analysis using SLD showed that the optimal preparation formula for baby telon tree tea oil (Melaleuca alternifolia Cheel) was obtained with a VCO and Olive Oil composition of 78.4% and 19.6% with a specific gravity response value of 0.906 gr/ml, viscosity 36.84 cp and volume transferred 57.33 ml. In the hedonic testing of baby telon oil preparations, tree tea oil (Melaleuca alternifolia Cheel) with variations of VCO and olive oil from the optimum formula in terms of color was preferred more by the panelists.